EFEKTIVITAS SENAM AEROBIK INTENSITAS SEDANG TERHADAP INDEKS MASSA TUBUH DAN KADAR GULA DARAH PADA MAHASISWI OVERWEIGHT DI JURUSAN GIZI POLTEKKES KEMENKES SEMARANG - Ismoyowati, Catur Sri; Sulistyowati, Enik; Rahmawati, Ana Yuliah (JURNAL RISET GIZI, 2018)
Background: Globalization leads to dietary deviations and physical activity that affect overweight. Preliminary study (2018) shows the prevalence of overweight according to Body Mass Index (IMT) at age 18 years old at Nutrition student of Poltekkes Kemenkes Semarang 17,2%. Obesity is closely related to body mass index and blood sugar levels. Lack of physical activity as one of the factors that trigger the incidence of obesity. Physical activity such as moderate aerobic aerobic exercise can leads to decreased saving fat so that automatically lose weight that will affect BMI and blood sugar levels during (GDS).Objective: To know the influence of moderate aerobic aerobic exercise on body mass index and blood sugar level in overweight student at Nutrition Department of Poltekkes Kemenkes Semarang. Methods: The type of research is True-Experimental with pre and post-control group design design. Sampling using random sampling technique to get 17 treatment samples and 17 control samples. The data collected were anthropometric data, energy intake and physical activity. The statistical tests used were Paired t-test, Wilcoxon, independent t-test and Mann Whitney test.Results: There was no difference in BMI in both treatment and control groups before and after medium intensity aerobic exercise p = 0.221 and control group p = 0.260. There was a difference of GDS in the treatment group before and after medium intensity aerobic exercise p = 0.018 and control group p = 0.041. There was no difference of IMT decrease between treatment and control group (p value = 0,994). There was no difference of GDS decrease between treatment and control group (p value = 0.679).Conclusion: There was no difference of IMT decrease between treatment and control group (p value = 0,994). There was no difference of GDS decrease between treatment and control group (p value = 0.679).